SELECTED FACTORS OF THE SOCIALIZATION IMPACT OF COMPUTER GAMES AND THEIR CONTENT - Noga, Henryk (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Playing computer games is a very popular way of spending free time among teenagers. Taking a role of a hero in a game may be a source of behavioural patterns, may influence a system of values in life and may have an impact on teenagers attitudes towards others. It is important to examine what kind of features and values heroes represent and also what are the teenagers’ preferences when it comes to the type of heroes in computer games.